Integrating co-design into formative research for a SBCC entry-point platform for nutrition-sensitive social protection programs in low -and middle-income country settings - Tahir Turk; Rina Paul; Nilofer Fatimi Safdar; Nadia Shah; Syed Mahbubul Alam; Sohel Reza Choudhury; Kashif Shafique; Zaeema Ahmer; Anthony Wenndt; Hamidullah Khan Babar; Tannaza Sadaf; Moniruzzaman Bipul (PLoS ONE, 2025)
Background Achieving adequate nutrition for vulnerable populations is an objective of the Sustainable Development Goals. Nutrition-sensitive social protection programs, including those that promote nutrition through Social and Behaviour Change Communication (SBCC), have the potential to reduce malnutrition and provide social supports to those most in need. Country-level needs assessments can clarify key issues. When supported by co-design approaches, program formative research may provide more culturally contextualised SBCC for the improved delivery of nutrition social protection to vulnerable groups. This formative study from Pakistan and Bangladesh, integrated co-design to more fully explore program beneficiary knowledge, attitudes and perceptions toward nutrition social protection to inform the design of SBCC key messages and an entry-point platform to ensure effective message dissemination. Methods Qualitative formative research was conducted to support findings from a systematic review. Thirty semi-structured interviews with program stakeholders and 12 focus group discussions (134 participants) were conducted with program beneficiaries in Bangladesh and Pakistan. Co-design sessions supplemented the needs assessment protocol. A COREQ checklist ensured best practice approaches in research design, analysis and reporting. NVIVO 2023 qualitative software supported the thematic analysis. Results Four organising themes were identified: 1. Barriers to Program Engagement, 2. Opportunities for Program Improvement, 3. Knowledge Attitudes and Practices, and 4. Target Groups, Messaging and SBCC Entry-Points, with 21 sub-themes emerging under the four organising themes. Main barriers related to resource constraints and maladministration of SPPs while opportunities identified greater integration of cash transfers with nutritious food provision, increased engagement with key influencers in vulnerable communities, and identification of culturally nuanced messages with dissemination through preferred channels. Integrating co-design sessions provided greater ownership, participation and engagement by program beneficiaries and more pragmatic SBCC solutions to challenges identified. Conclusion The needs assessments and integrated co-design sessions highlighted the benefits of close consultation with program beneficiaries in the design of culturally appropriate SBCC interventions to support nutrition-sensitive social protection programs. A SBCC entry-point platform was developed from participant recommendations to provide options for programmers on message designs, advocacy approaches and dissemination channels with the approaches applicable for a number of low -and middle-income countries where malnutrition is a major challenge.